2020
DOI: 10.33029/0016-9900-2020-99-1-37-44
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity in Copper Production Workers Exposed to Heavy Metals

Abstract: Introduction. Cardiovascular diseases (CVD) are a leading cause of morbidity and mortality. The role of occupational hazards in the CVD prevalence remains to be clarified. Material and methods. Here we report the results of the study of risk factors and CVD prevalence in 590 workers at the largest copper production plants in the Sverdlovsk region, exposed to heavy metals in the workplace. The workers` health information was obtained during a regular medical examination in 2018. The lead concentration increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The study suggested that the observed CVDs were attributed to the toxic effects of heavy metals especially Pb and Cd. 75 Concerning the medical history and examination in the current work, almost all cardiovascular and general manifestations (apart from edema of lower limbs and dizziness) showed a statistically significant elevated prevalence (P < 0.05) among the exposed Cu smelter workers when compared with the controls (Table 2). Approximately 34% of the exposed workers (n = 14) gave a history of exertional dyspnea, whereas 44% (n = 18) of the workers experienced chronic cough and 34% had recurrent expectoration.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The study suggested that the observed CVDs were attributed to the toxic effects of heavy metals especially Pb and Cd. 75 Concerning the medical history and examination in the current work, almost all cardiovascular and general manifestations (apart from edema of lower limbs and dizziness) showed a statistically significant elevated prevalence (P < 0.05) among the exposed Cu smelter workers when compared with the controls (Table 2). Approximately 34% of the exposed workers (n = 14) gave a history of exertional dyspnea, whereas 44% (n = 18) of the workers experienced chronic cough and 34% had recurrent expectoration.…”
Section: Discussionmentioning
confidence: 74%
“…Twenty-four–hour ECG Holter monitoring revealed an elevated mean heart rate and more frequent premature supraventricular and ventricular contractions among Cu smelter workers compared with the healthy control subjects 76 . In another study on the prevalence and risk factors of CVDs, hypertension was detected among 57% of the examined 590 workers who were employed at the largest Cu production plants in the Sverdlovsk region 75 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…When there is a systemic Cu de ciency, it can cause Cu metabolism disorders [5]. But Cu must be a trace amount in the body, and when the amount exceeds the needs of cells, it can also cause toxic damage to the liver and other organs [6,7]. The former represents Menkes disease, the latter is Wilson disease.…”
Section: Introductionmentioning
confidence: 99%